20-40-60-minute dinners : meals to match the time you have - Otterstrom, Kate (Shadow Mountain Publishing, 2023)
"Whether you only have twenty minutes or an hour-or something in between-you can deliver a delicious entrée and side dish to the table with these quick, easy, and crowd-pleasing recipes. Organized by "available time" rather than by "kind of dish," this unique cookbook is designed to help the time-conscious cook with dinner planning. Since Kate is gluten-intolerant herself, each recipe also includes instructions on how to adapt it for a gluten-free option, along with a dedicated space for you to jot down notes for additional variations." --